Nanotechnology-An Overview - Krishna Sailaja; A. Saritha Reddy; V. Sreelola; P. Swathi; Ch. Vineela (Journal of Pharmacy and Nutrition Sciences, 2014)
Nanotechnology provides a wide technological platform for varying range of potential applications. Nanotechnology is the design, characterization, synthesis and application of materials, structures, devices and systems by controlling shape and size at nanometer scale, 1-100nm. Nanotechnology is being employed in the pharmaceutical field to improve drug solubility, bioavailability and delivery to various sites of action. To overcome the limitations in cellular uptake of highly active molecules, the use of nano carriers is the focus of modern drug delivery. Strategies like Nanosponges for enhancing solubility of poorly water soluble drugs, Nanocantilevers for detection of biomarkers of cancer, Quantum dots for medical imaging, Dendrimers for photodynamic therapy and gene transfection, Solid lipid nanoparticles as cosmeceuticals are employed. Nanodevices like respirocytes and microbivore are used for temporary replacement for natural blood cells in case of emergencies. In this review, therapeutic applications of various nano-structured materials have been discussed.